Peningkatan Produksi Padi Melalui Penguatan Kelembagaan Perbenihan Padi Di Nagari Lubuk Pandan, Kecamatan 2 X 11 Enam Lingkung - Ivonne Ayesha (Jurnal Pembangunan Nagari, 2018)
This study aims to identify the institutions that play a role in the procurement of rice seeds, describe the role of each institution, and develop policy recommendations for institutional strengthening of rice seed. The research was conducted in Nagari Lubuk Pandan, District 2x11 Six Lingkung, Padang Pariaman District, West Sumatera Province. The respondents' farmers were deliberately determined by 35 people based on the guidance of Wali Nagari and community leaders. Data were analyzed descriptively and presented in table and diagram. The results showed that 1) Institutional of rice seed in Nagari Lubuk Pandan consist of formal and informal institution. The formal institutions are Gapoktan "Lubuk Pandan Sejahtera" and Saprodi Kiosk. Informal institutions are groups of other farmers who lend rice seeds. More than half of the farmers of the respondents obtained rice seed from other farmers, because it was more efficient, 2) Gapoktan "Lubuk Pandan Sejahtera", played a role in channeling seeds to its members if there is a seed assistance program from the government. Saprodi Kiosk provides high quality rice seeds at all times, but very few farmers can afford them, and 3) Farmers' structural weaknesses (low education and knowledge, narrow land, technological mastery and low group manageability), cause they are unable to integrate the provision of seed input with the farm, so that production tends to decrease. This condition needs to be improved through institutional strengthening and empowerment of farmers through concepts acceptable to farmers